Calculus for business, economics, life sciences and social sciences - Barnett, Raymond A.; Ziegler, Michael R.; Byleen, Karl E. (Upper Saddle River, N.J. Pearson Education, 2011)
This text covers calculus with an emphasis on cross-discipline principles and practices. It develops a thorough, functional understanding of mathematical concepts in preparation for their application in other areas.
Keywords: Calculus; Calculus -- Problems, exercises, etc